Rural Households’ Attitude to Diversification into Non-farm Enterprises in Katsina State, Nigeria - Danlami Haruna Yakubu; Nasiru Musa; Bello Zaki Abubakar; Muhammad Sani Muhammad Jabo (Journal of Agricultural Extension, 2022)
The study investigated the rural households’ attitude to diversification into non-farm enterprises in Katsina State, Nigeria. A multistage sampling procedure was used to select 256 farmers for the study. Data were obtained with the aid of questionnaire and analyzed using percentage and regression analysis. The most positive attitude was “that non-farm enterprise is a crucial pathway to food security for rural households”.  It was closely followed by “non-farm enterprise is a source of agricultural household savings used for food purchase in hard times” and “non-farm enterprise provides a means to cope or survive when farming fails”. Farmers expressed positive attitude to diversification into non-farm enterprises and do not depend on agriculture as a sole means of livelihood but diversified income sources; the diversified farmers had higher income level. Government should support the existing non-farm enterprises and encourage creation of new ones; also improve formal credit access. Furthermore, technical support and skills acquisition training programs should be provided to enhance the performance and efficiency of non-farm enterprises in rural areas.